Analisa Unjuk Kerja Peningkatan Transmisi Citra pada Kanal Wireless Menggunakan Teknik Diversity Selection Combining - Baharuddin Abbas (Jurusan Teknik Elektro Universitas Andalas, 2017)
This study is the simulation of SPIHT image compression using diversity selection combining techniques. The image is compressed by using SPIHT compression techniques after wavelet decomposition. By giving Rayleigh fading channel and AWGN on the channel transmission will cause the degradation of the overall system performance. To minimize the effects caused by the errors that occur during the transmission, the diversity selection combining techniques are used at the receiver that work on the wavelet domain in order to increase the overall system performance. Performance evaluation on the use of selection combining diversity technique can be determined through PSNR analysis. The simulation results of this study indicate that applying the diversity selection combining techniques on the system that affected by noise AWGN and Rayleigh fading can increase the performance of the overall system at the receiver when comparing to the receiver without using the selection combining diversity techniques.Keywords : Diversity Selection Combining, Noise AWGN, Fading Rayleigh, PSNR, BERAbstrak – Penelitian ini merupakan simulasi citra terkompresi SPIHT menggunakan teknik diversity selection combining. Citra yang digunakan dikompresi terlebih dahulu dengan teknik kompresi SPIHT setelah didekomposisi wavelet. Pada kanal transmisi diberi pemodelan kanal Rayleigh fading dan AWGN yang akan menyebabkan terjadinya penurunan unjuk kerja sistem secara keseluruhan. Oleh karena itu, untuk memperbaiki unjuk kerja sistem tersebut yaitu dengan meminimalkan efek yang diakibatkan oleh error yang terjadi selama transmisi, maka pada bagian penerima digunakan teknik diversity selection combining yang bekerja pada daerah wavelet. Besarnya pengaruh dari teknik diversity selection combining yang digunakan dapat diketahui melalui analisa PSNR. Hasil simulasi dari penelitian ini menunjukkan bahwa, adanya peningkatan perbaikan sistem dipenerima bila dibandingkan dengan tanpa menggunakan teknik diversity selection combining.Kata kunci : Diversity Selection Combining, Noise AWGN, Fading Rayleigh, PSNR, BER